Monumento Transit Connection - Frivaldo, Charles Simon D.; Laureano, Janrey F.; Melendres, Ismael III A. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 2, 2005)
The Phase 2 of the MRT3 Line is part of the completion of the transit network in Metro Manila. In this project, the MRT3 Line, running along EDSA, will be extended from North Avenue to Monumento. With the line terminating at Monumento, the transit would definitely have an impact on this area. Among the major considerations for Monumento were the preparation of the district for the transit, the impact the station would have on the Bonifacio Monument and the connection of the two transit terminals, particularly LRT1 and MRT3. For the district, the rehabilitation of the area in terms of utilization of spaces and consideration for pedestrian and vehicular circulation were some of the concerns. For the monument, the need to provide the best approach in preserving the Bonifacio monument was of great importance. For the lines, the creation of a physical link between the two lines as well as its impact on the site was an important consideration. In this study, the aim was to create a scheme that would resolve the issues present in the site. The scheme was one that managed to create a strong relationship between the major elements in the site, particularly the two lines, the monument and the different quadrants. From this scheme, the design of the area was to be developed. The design of the Monumento area would include the site development plan, transit terminal and connection design and guidelines for buildings and means of public access.